PELA- GANDONG AND HARMONIZATION LIFE OF BROTHERHOOD (ORANG BASAUDARA) (Study case The Relations of Islam and Christianity post conflict in Ambon) - Attamimy, M. (Al-Ulum, 2014)
In post conflict period, Moluccas people were re-echoed the desire to be a civilized society and a dignified. Moluccas Community believes that the spirit of Pela-Gandong is able to glue back the kinship that had marred. Pela is cultural friendships which have been institutionalized in every heart, mind, and behavior of the Moluccans, itâs mean that they come from the same culture, although their religion is different. Pela-Gandong is a âmental awareness âof the âorang Basudaraâ were so strong, so whatever the burden and responsibility of the âorang Basudaraâ is a shared of responsibility. This Relationship has relevance to the teaching of religion in ukhuwwah concept. Therefore, the embodiment of teaching of Pela and the values which contained itâs none other the practice of religion. Instead, the reluctance to hold of Pela tradition, itâs same as reluctant to implement the values of religion itself.Â ----------Keinginan masyarakat MalukuÂ  untuk kembali menjadi masyarakat yang beradab dan bermartabat kembali dikumandangkan pascakonflik. Masyarakat meyakini bahwa spirit Pela-Gandong mampu merekatkan kembaliÂ  tali persaudaraanÂ  yang sempat tercederai. Pela-Gandong adalah persahabatan kultural yangtelahÂ  melembaga dalam setiap hati, pikiran, dan perilaku masyarakat Maluku, yaituÂ  bahwa mereka berasal dari budaya yang sama walaupun agama yang mereka anutÂ  berbeda. Pela-Gandongpanggilan jiwa orang Basudara, yang begitu kuat, sehingga apapun yang menjadi beban dan tanggung jawab orang Basudara merupakan tanggung jawab bersama.Ikatan seperti ituÂ  memiliki relevansi dengan ajaran agama dalam konsep ukhuwwah. Oleh karena itu, pengejawantahan ajaran Pela dan nilai-nilai yang terkandung di dalamnya tidak lain merupakan pengamalan ajaran agama. Sebaliknya, keengganan untuk memegang tradisi Pela, sama dengan enggan melaksanakan ajaran agama itu sendiri